Dette nummers samlede anmeldelser - Plambech, Sine; Arnfred, Signe (Kvinder, Køn & Forskning, 2011)
I dette nummer er følgnde bøger blevet anmeldt:Jo Doezema: Sex Slaves and Discourse Masters – The Construction of Trafficking. Zed Books. London & New York. 2010.Naila Kabeer et al (eds.): Global Perspectives on Gender Equality. Reversing the Gaze. Routledge. 2008.Jane Parpart and Marysia Zalewski (eds.): Rethinking the Man Question. Sex, Gender and Violence in International Relations. Zed Books, 2008.